Implementation of Demonstration Method Accompanied by Teaching Aids to Improve Mathematics Learning Outcomes inState Elementary School 02 Cantuk - Ferda Devitasari Renata Putri; Wiputra Cendana (Journal of Creative Power and Ambition (JCPA), 2026)
The low mathematics learning outcomes of elementary school students are caused by monotonous learning and a lack of active student involvement. This study aims to improve students' mathematics learning outcomes through the application of demonstration methods accompanied by teaching aids at SDN 2 Cantuk. This study used the Classroom Action Research (CAR) method, implemented in two cycles. The subjects were 25 fourth-grade students at SDN 2 Cantuk. Data were collected through observation, learning achievement tests, documentation, and interviews. The results showed that the application of demonstration methods accompanied by teaching aids was able to improve students' mathematics learning outcomes. In pre--cycle, average value-The average score for students was 62 with a learning completion rate of 48%. In cycle I, the average score-The average score increased to 74 with a learning completion of 72%. Furthermore, in cycle II, the average score-The average student score increased to 86, with learning completion reaching 92%. Student activity and participation during learning also increased. Based on these research results, it can be concluded that the demonstration method accompanied by teaching aids is effective in improving elementary school students' mathematics learning outcomes.